Robots = Robotlar - Wedge, Chris (Hollywood, LA : Twentieth Century Fox, 2005)
In a robot world, a young idealistic inventor travels to the big city to join his inspiration's company, only to find himself opposing its sinister new management.
K-3.
Language : Turkish, English, Estonian, Magyar, Polski.
Subtitle : Turkish, English, Estonian, Magyar, Polski, Latvian, Lithuanian.
Keywords: Animated films; Movie -- animated films; Robots -- Animated movie